Analysis of the Dynamics of Water Flow and Suspension Flow Discharge in Volcano Watershed with Settlement Land Use - La Ode Hadini; Junun Sartohadi; Muhammad Anggri Setiawan; Djati Mardiatno; Nugroho Crhristanto (Department of Geography Education, University of Jember, 2023)
Suspension flow into the upstream of volcano watershed is sensitive to land use. In Indonesia, a settlement is a form of land use in several volcanic landscapes. There is currently no detailed study on the suspension flow sediment from the settlement land use. The purpose of this study is to investigate the characteristics of the relationship between water and suspension flow discharge. The study was conducted through the measurements at a gully outlet that produced 747 suspension load data. For each rainfall event, suspension load measurements were made in the field, followed by laboratory analysis. Additionally, field surveys were used to determine the characteristics of settlement land use and the water flow into the gully system. According to the findings, the peak flow discharge corresponds to the peak suspension discharge, the peak flow discharge comes before the peak suspension discharge, and the peak flow discharge happens after the peak suspension discharge. The average time lag between initial rainfall events and suspension flow was 10.36 minutes, and the suspension peak content varied by an average of 2.22 gl-1. The grain size was also dominated by the clay fraction, averaging 67.86% on the ascending branch and 67.82% on the descending branch.